Traditional food products on the local market - consumption conditional on the characteristics of management and restaurant facilities in tourism of Vojvodina (Serbia) - Kalenjuk Pivarski, Bojana; Tekić, Dragana; Šmugović, Stefan; Novaković, Aleksandra; Ivanović, Velibor; Petrović, Marica; Banjac, Maja; Đerčan, Bojan; Tešanović, Dragan; Ćirić, Miloš; Čabarkapa, Ivana; Ćirić, Ivana; et al. (Frontiers in Sustainable Food Systems, 2023)
The research dealt with traditional food products (TFP) observed on the local hospitality-touristic market, from the point of view of 300 restaurant workers employed in managerial positions, as important subjects in preservation of tradition in hospitality and touristic industry of Vojvodina (Republic of Serbia). The research examined the management’s views on TFP, as well as whether there are differences based on the features of the respondents as well as the restaurant facility. In order to obtain data that would provide additional guidelines for acting on the hospitality and tourism market, the procurement and consumption of TFP was also examined. In order to determine set differences the non-parametric Kruskal-Wallis test was applied. In order to establish statistically significant differences between the observed groups, the Dunn’s post hoc test was applied. In the second part of the research, a binary logistic regression model was applied in order to determine which of the observed variables has a significant impact on the respondents’ decision to acquire TFP from their field. The research showed that the level of education and the field of management education significantly influence the attitudes about the offer of TFP in the hospitality and tourism market, as well as the type of restaurant offer and the development of the field of business.